Android smartphones - DiMarzio, J. F. (--For dummies., 2023)
Android Smartphones For Dummies is the all-new guide to Android phones with the familiar Dummies charm everyone loves. This book will give Android rookies a crash-course in how to use these popular phones. You'll go beyond the basics of texting and taking photos--we'll walk you through all the pro tips and tricks for customizing your phone, optimizing all your settings, using social media (safely), and making the most of apps and widgets. We'll even teach you how to make calls, because phones can still do that.